Mengenal Penyebab tentang Resiko Penyakit ARDS di Usia Lanjut - Mellisa Intan Permatasari; Nabila Aulia Rasya; Zal Sabilla Putri Febrianti; Dwi Ratih Rahayu; Dhionisius David Mario; Liss Dyah Dewi Arini (Lembaga Pengembangan Kinerja Dosen, 2024)
Acute Respiratory Distress Syndrome (ARDS) is a life-threatening condition characterized by severe inflammation and damage to the alveoli, leading to impaired oxygen exchange in the lungs. Older adults are particularly vulnerable to ARDS due to age-related physiological changes and the presence of comorbidities. This literature review aims to explore the risk factors, pathophysiology, and management strategies of ARDS in the elderly population. The review identifies key factors such as immunosenescence, decreased lung elasticity, and the presence of chronic conditions like hypertension, diabetes, and cardiovascular disease as contributing to the increased susceptibility to ARDS in older adults. Infections, especially pneumonia and sepsis, are found to be significant triggers for the onset of ARDS. Additionally, environmental factors, such as long-term exposure to air pollution and smoking, further elevate the risk. Prevention through vaccination and the management of comorbidities are highlighted as essential strategies for reducing the incidence of ARDS. The review also emphasizes the importance of lung-protective ventilation strategies in the treatment of ARDS in older adults. Overall, this paper underscores the need for comprehensive healthcare approaches, including early detection, vaccination, and integrated care for managing comorbid conditions to mitigate the impact of ARDS in the elderly. Further research is recommended to develop more effective and tailored treatment approaches for this vulnerable population.